Analisis Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Ulang Pelanggan Produk Dummy Cake Melalui Kepuasan Pada United Foam (Studi Kasus Yang Bertransaksi Di Tokopedia) - Kelvin Liennt; Theresia Pradiani; Yunus Handoko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Marriage and birthdays are sacred moments and important celebrations. One tradition observed during wedding or birthday parties is the cake-cutting tradition. A fake wedding cake is also a good option if you want to showcase a large and beautiful cake but have a smaller guest list. The purpose of this research is to determine and analyze: 1) the influence of product quality on consumer repurchase decisions, 2) the influence of service quality on consumer repurchase decisions, 3) the influence of product quality on consumer satisfaction, 4) the influence of service quality on consumer satisfaction, 5) the influence of consumer satisfaction on consumer repurchase decisions, 6) the influence of product quality on consumer purchase decisions, and 7) the influence of product quality on consumer purchase decisions, mediated by consumer satisfaction on Tokopedia. The research method used in this study is path analysis; the researcher used path analysis (SPSS ver. 26) to determine cause-and-effect relationships. To obtain reliable research results, validity and reliability tests. The hypothesis results show that 1) product quality has an influence but not significant on consumer repurchase decisions, 2) product quality has a significant influence on consumer repurchase decisions, 3) product quality has a significant influence on consumer satisfaction, 4) service quality has a significant influence on consumer satisfaction, 5) consumer satisfaction has a significant influence on consumer repurchase decisions, 6) product quality does not influence consumer satisfaction through consumer satisfaction, and 7) service quality does not influence consumer satisfaction through consumer satisfaction. Keywords: Product Quality, Service Quality, Consumer Satisfaction, Repurchase Decisions.